2013
DOI: 10.1111/mmi.12143
|View full text |Cite
|
Sign up to set email alerts
|

On the role of TolC in multidrug efflux: the function and assembly of AcrABTolC tolerate significant depletion of intracellular TolC protein

Abstract: TolC channel provides a route for the expelled drugs and toxins to cross the outer membrane of Escherichia coli. The puzzling feature of TolC structure is that the periplasmic entrance of the channel is closed by dense packing of twelve α-helices. Efflux pumps exemplified by AcrAB are proposed to drive the opening of TolC channel. How interactions with AcrAB promote the close-to-open transition in TolC remains unclear. In this study, we investigated in vivo the functional and physical interactions of AcrAB wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…Thus, the slower diffusion state here must not be dominated by CusA trimer clustering. Past biochemical studies (7) have shown that, for the RND family drug efflux complex AcrBA-TolC, the innermembrane pump AcrB can directly interact with the outermembrane channel protein TolC in the absence of the adaptor protein AcrA (39,40). A protein docking model (24) also showed that CusA can interact with CusC directly.…”
Section: Results and Analysismentioning
confidence: 99%
“…Thus, the slower diffusion state here must not be dominated by CusA trimer clustering. Past biochemical studies (7) have shown that, for the RND family drug efflux complex AcrBA-TolC, the innermembrane pump AcrB can directly interact with the outermembrane channel protein TolC in the absence of the adaptor protein AcrA (39,40). A protein docking model (24) also showed that CusA can interact with CusC directly.…”
Section: Results and Analysismentioning
confidence: 99%
“…E. coli cells lacking the TolC channel, which is involved in efflux of antibiotics and export of proteins as a part of the type I secretion pathway, are more resistant to vancomycin (2–4-fold increase in minimal inhibitory concentrations) than the wild-type cells, suggesting some penetration of this ~1200 Da molecule through TolC. 47,48 Interestingly, this penetration requires the presence of active AcrAB transporter, further suggesting that vancomycin slips through TolC when it is engaged by the AcrAB pump (see also below). It is possible that permeation through other specific porins and TonB-dependent channels and the Bam complex responsible for the assembly of the outer membrane and at protein–LPS interfaces also contribute to the intracellular accumulation of antibiotics.…”
Section: The Two-membrane Barrier Of Gram-negative Bacteriamentioning
confidence: 99%
“…The susceptibilities of E. coli cells to different classes of antibiotics were determined by a 2-fold broth dilution method (22) with the following modifications. For consistency with previous studies of the laboratory E. coli strains (23)(24)(25), cells were grown in LuriaBertani (LB) broth (tryptone, 10 g/liter; yeast extract, 5 g/liter; NaCl, 5 g/liter) with appropriate selection markers, as needed, at 37°C with shaking at 200 rpm. When needed, when the cells had an optical density at 600 nm (OD 600 ) of ϳ0.3, L-arabinose (up to 0.1%) was added to induce the expression of the pore and the cells were further incubated until the OD 600 reached 1.0.…”
Section: Methodsmentioning
confidence: 99%